Sociodemographic and geographic characteristics associated with patient visits to osteopathic physicians for primary care - Licciardone John C; Singh Karan P (BMC, 2011)
Abstract Background Health care reform promises to dramatically increase the number of Americans covered by health insurance. Osteopathic physicians (DOs) are recognized for primary care, including a "hands-on" style with an emphasis on patient-centered care. Thus, DOs may be well positioned to deliver primary care in this emerging health care environment. Methods We used data from the National Ambulatory Medical Care Survey (2002-2006) to study sociodemographic and geographic characteristics associated with patient visits to DOs for primary care. Descriptive analyses were initially performed to derive national population estimates (NPEs) for overall patient visits, primary care patient visits, and patient visits according to specialty status. Osteopathic and allopathic physician (MD) patient visits were compared using cross-tabulations and multiple logistic regression to compute odds ratios (ORs) and 95% confidence intervals (CIs) for DO patient visits. The latter analyses were also conducted separately for each geographic characteristic to assess the potential for effect modification based on these factors. Results Overall, 134,369 ambulatory medical care visits were surveyed, representing 4.6 billion (NPE) ± 220 million (SE) patient visits when patient visit weights were applied. Osteopathic physicians provided 336 million ± 30 million (7%) of these patient visits. Osteopathic physicians provided 217 million ± 21 million (10%) patient visits for primary care services; including 180 million ± 17 million (12%) primary care visits for adults (21 years of age or older) and 37 million ± 5 million (5%) primary care visits for minors. Osteopathic physicians were more likely than MDs to provide primary care visits in family and general medicine (OR, 6.03; 95% CI, 4.67-7.78), but were less likely to provide visits in internal medicine (OR, 0.37; 95% CI, 0.24-0.58) or pediatrics (OR, 0.21; 95% CI, 0.11-0.40). Overall, patients in the pediatric and geriatric ages, Blacks, Hispanics, and persons in the South and West were less likely to utilize DOs, although there was some evidence of effect modification according to United States Census region. Conclusions Health care reform provides unprecedented opportunities for DOs to reach historically underserved populations and to overcome the "pediatric primary-care paradox."